Effectiveness of an Energy Management Training Course on Employee Well-Being: A Randomized Controlled Trial. Issue 1 (January 2019) - Das, Sai Krupa; Mason, Shawn T.; Vail, Taylor A.; Rogers, Gail V.; Livingston, Kara A.; Whelan, Jillian G.; Chin, Meghan K.; Blanchard, Caroline M.; Turgiss, Jennifer L.; Roberts, Susan B.
Purpose: Programs focused on employee well-being have gained momentum in recent years, but few have been rigorously evaluated. This study evaluates the effectiveness of an intervention designed to enhance vitality and purpose in life by assessing changes in employee quality of life (QoL) and health-related behaviors. Design: A worksite-based randomized controlled trial. Setting: Twelve eligible worksites (8 randomized to the intervention group [IG] and 4 to the wait-listed control group [CG]). Participants: Employees (n = 240) at the randomized worksites. Intervention: A 2.5-day group-based behavioral intervention. Measures: Rand Medical Outcomes Survey (MOS) 36-item Short-Form (SF-36) vitality and QoL measures, Ryff Purpose in Life Scale, Center for Epidemiologic Studies questionnaire for depression, MOS sleep, body weight, physical activity, diet quality, and blood measures for glucose and lipids (which were used to calculate a cardiometabolic risk score) obtained at baseline and 6 months. Analysis: General linear mixed models were used to compare least squares means or prevalence differences in outcomes between IG and CG participants. Results: As compared to CG, IG had a significantly higher mean 6-month change on the SF-36 vitality scale ( P = .003) and scored in the highest categories for 5 of the remaining 7 SF-36 domains: general health ( P = .014), mental health ( P = .027), absence of role limitations due to physical problems ( P = .026), and social functioning ( P = .007). The IG also had greater improvements in purpose in life ( P < .001) and sleep quality (index I, P = .024; index II, P = .021). No statistically significant changes were observed for weight, diet, physical activity, or cardiometabolic risk factors. Conclusion: An intensive 2.5-day intervention showed improvement in employee QoL and well-being over 6 months.